Protection of Personal Data in Mobile Health: a mini Review - Nurbaiti Nurbaiti (JATISI, 2026)
Mobile Health (mHealth) is recognized as an innovative approach to providing accessible, portable and cost-effective healthcare. Despite the many benefits associated with using a mobile device, there are major concerns about mhealth in the area of privacy and security. The purpose of this article is to find out how to protect personal data in the form of data security and privacy in personal health devices. The method used is a simple article review or mini literature review to find answers to scientific questions that match the purpose of this article using a database (PubMed, Researchgates and Google Scholar) with the literature of the last 10 years. The results of this study highlight some of the major weaknesses of mHealth. Most of the security systems are still weak, so endanger user privacy and security by violating data protection regulations.